Canine ovariohysterectomy: a survey of surgeon concerns and surgical complications encountered by newly graduated veterinarians - Blacklock, Kelly L. Bowlt; Langer, Pierre; Halfacree, Zoe; Yool, Donald A.; Corr, Sandra; Owen, Laura; Friend, Ed; Ekiri, Abel (University of Toronto Press, 2016)
The objective of this study was to document newly qualified veterinarians’ concerns and surgical complications encountered during canine ovariohysterectomy (cOVH) during the first year of general practice. A questionnaire investigating concerns about cOVH procedures was sent to all final-year veterinary students (group 1) enrolled at five UK universities. Participants were later asked to complete a similar questionnaire 6 months (group 2) and 12 months (group 3) after graduation, which involved grading their concern about different aspects of the cOVH procedure and reporting surgical complications encountered after completing three cOVHs. Responses were compared between different time points. There were 196 respondents in group 1, 55 in group 2, and 36 in group 3. Between groups 1 and 2, there was a statistically significant reduction in the respondents’ levels of concern in every aspect of cOVH (p < .05). Between groups 2 and 3, there was no statistically significant change in respondents’ levels of concern in any aspect of cOVH (pb.21). There was a significant reduction in the number of complications encountered by veterinarians in group 3 (39/102, 38.2%) compared to those in group 2 (117/206, 56.8%) (p ¼ .002). Employers should anticipate high levels of concern regarding all aspects of cOVHs in new graduates, and supervision during the first 6 months may be particularly useful.